Ce3 +-rich cubic phase lanthanum ferrite magneto-optical film, preparation method and application
By preparing the cubic phase lanthanum ferrite magneto-optical film La2-xCexFe2-xVxO6 rich in Ce3+, the existing magneto-optical isolation devices have high losses, poor isolation and difficulty in the integration process during the monolithic integration process, and high-quality magneto-optical film preparation and good photoelectric performance are achieved.
Patent Information
- Application Number
- CN202411942467.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the process of monolithic integration, existing magneto-optical isolation devices have problems such as high losses, poor isolation, and difficulty in integration process. In particular, Ce3+ is metastable, causing heterogeneous phase generation, affecting magneto-optical performance, and the thermal expansion coefficient and unit cell parameters of the garnet film and the Si substrate are very different, resulting in the film being prone to cracking.
A cubic phase lanthanum ferrite magneto-optical film La2-xCexFe2-xVxO6 rich in Ce3+ was proposed. Through specific stoichiometric ratios and preparation methods, including multiple grinding, pressing, sintering and radio frequency magnetron sputtering, a film with a cubic double perovskite structure was prepared, and annealed with quartz glass and single crystal silicon as the substrate to ensure the high quality and optimal orientation of the film.
It has achieved high-quality magneto-optical thin film preparation, with good optical transmission performance, strong saturation magnetization and obvious magnetic anisotropy. It is suitable for silicon-based photoelectric integrated devices, solving the problem that monolithic integrated magneto-optical isolation devices are difficult to break through.
Smart Images

Figure CN119717312A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magneto-optical materials, and particularly relates to a Ce-rich 3+ Cubic phase lanthanum ferrite magneto-optical film, preparation method and application. Background Art
[0002] Magneto-optical materials are an important functional material for optical information. Magneto-optical photonic devices with magneto-optical materials as the core, such as magneto-optical isolators, magneto-optical circulators, magneto-optical switches and magneto-optical modulators, are widely used in optical fiber communications, computer technology, national defense, lasers and other fields. At present, with the rapid development of information technology, the size of devices has been reduced to less than a dozen nanometers. The speed, power consumption and heat dissipation of devices have become bottlenecks restricting the development of integrated circuit technology. Therefore, silicon-based optoelectronic technology with advantages such as low cost, large size, good waveguide characteristics, excellent light-guiding performance and radiation resistance has become an important trend in the development of the new generation of information, and the monolithic integration of silicon-based magneto-optical integration is the focus and difficulty of silicon-based optoelectronic technology. Among them, magneto-optical isolators, as important basic components in optical communications, are called "a major problem in the field of integrated optics" due to many constraints such as high loss, poor isolation and difficult integration process.
[0003] At present, traditional commercial isolation devices are based on YIG (Y3Fe5O 12 ) and Bi 3+ :YIG (Bi 3+ :Y3Fe5O 12 ) and other garnet magneto-optical crystals to achieve optical isolation. In recent years, research has found that magnetic ions Ce 3+ It has the function of enhancing magneto-optical effect, thus Ce with large Faraday rotation angle and low optical loss 3+ :YIG thin film has gradually become a research hotspot for the new generation of magneto-optical materials. 3+ The garnet film is metastable, which makes it easy to generate CeO2 and iron oxide impurities during the preparation process, affecting the magneto-optical properties. In addition, the thermal expansion coefficient between the garnet film and the Si substrate (YIG: 10.4×10 -6 K -1 , Si: 3×10 -6 K -1 The huge difference in the crystal structure and cell parameters (YIG: 12.376Å, Si: 5.431Å) also makes the garnet-type magneto-optical film grown directly on a silicon single wafer prone to cracking. All these factors make it difficult to make a breakthrough in monolithic integrated magneto-optical isolators. Summary of the invention
[0004] In view of the above situation, the main purpose of the present invention is to provide a Ce-rich 3+The present invention provides a cubic phase lanthanum ferrite magneto-optical film, a preparation method and an application thereof to solve the above technical problems.
[0005] The present invention proposes a Ce-rich 3+ A cubic phase lanthanum ferrite magneto-optical film, wherein the lanthanum ferrite magneto-optical film is La 2-x Ce x Fe 2-x V x O6; Among them, La 2-x Ce x Fe 2-x V x O6 ( x =0.6~1); The raw materials for preparing lanthanum ferrite magneto-optical film include La2O3, CeO2, Fe2O3, Fe and V2O5, and are prepared on quartz glass and single crystal silicon as substrates. The crystal phase is a cubic double perovskite structure with a space group of Fm -3 m ; Among them, Ce and La jointly occupy the A site, and Fe and V jointly occupy the B site.
[0006] The present invention proposes a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film is provided, and is used to prepare the above-mentioned cubic phase lanthanum ferrite magneto-optical film, and the method comprises the following steps: Step 1. Follow La 2-x Ce x Fe 2-x V x The raw materials La2O3, CeO2, Fe2O3, Fe and V2O5 are weighed in a stoichiometric ratio of O6, and the weighed raw materials La2O3, CeO2, Fe2O3, Fe and V2O5 are ground once in a corundum mortar to obtain a once-ground raw material; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering using quartz glass, Si (100) or Si (111) oriented single crystal silicon as the substrate and Ar as the working gas. 2-x Ce xFe 2-x V x O6 film; Step 4: Use a quartz vacuum tube furnace to 2-x Ce x Fe 2-x V x O6 thin film is annealed to obtain a completely crystallized La 2-x Ce x Fe 2-x V x O6 film.
[0007] The present invention also provides an application of a cubic phase lanthanum ferrite magneto-optical film, using the above Ce-rich 3+ A Ce-rich lanthanum ferrite magneto-optical film prepared by a method for preparing a cubic lanthanum ferrite magneto-optical film 3+ The cubic phase lanthanum ferrite magneto-optical film is used in optical isolators, optical circulators or magneto-optical modulators.
[0008] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The Ce-rich 3+ Cubic lanthanum ferrite magneto-optical thin film La 2-x Ce x Fe 2-x V x O6 is a new type of magneto-optical thin film material with a cubic double perovskite structure and a space group of Fm -3 m (225); The lattice mismatch between the magneto-optical film and the silicon substrate is small. The silicon-based film obtained after crystallization has obvious preferential orientation, high film quality, small roughness, and no cracks or wrinkles.
[0009] 2. The magneto-optical thin film material of the present invention has good optical transmittance and strong saturation magnetization, as well as obvious magnetic anisotropy and strong magneto-optical effect, and is expected to be applied in the field of silicon-based optoelectronic integrated devices.
[0010] 3. The preparation method of the present invention has simple and rapid process, low cost, short cycle and good reproducibility.
[0011] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description or learned through embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 After crystallization, La 2-x Ce x Fe 2-x V x XRD spectrum of O6 / SiO2 film; Figure 2 (a) XRD spectrum and (b) GIXRD spectrum of LaCeFeVO6 / Si film; Figure 3 SEM cross-sectional morphology of LaCeFeVO6 thin films (sputtered for 1 h) after crystallization prepared on (a) Si(100) and (b) Si(111) substrates; Figure 4 AFM3D morphology of LaCeFeVO6 / Si(100) films after crystallization after sputtering for (a) 1h and (b) 3h; Figure 5 XPS spectra of (a) La, (b) Ce, (c) Fe, (d) V, and O elements in LaCeFeVO6 / Si(100) film; Figure 6 is the transmittance curve of the crystallized LaCeFeVO6 / Si film; Figure 7 Saturation hysteresis loops of LaCeFeVO6 films prepared on (a) Si(100) and (b) Si(111) substrates; Figure 8 This is the MCD spectrum of LaCeFeVO6 / SiO2 film. DETAILED DESCRIPTION
[0013] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0014] These and other aspects of the embodiments of the present invention will be apparent with reference to the following description and accompanying drawings. In these descriptions and accompanying drawings, some specific implementations of the embodiments of the present invention are specifically disclosed to represent some ways of implementing the principles of the embodiments of the present invention, but it should be understood that the scope of the embodiments of the present invention is not limited thereto.
[0015] Embodiment 1 A Ce-rich 3+ Cubic phase lanthanum ferrite magneto-optical film, lanthanum ferrite magneto-optical film is La 2-x Ce x Fe 2-x V x O6; Among them, La 2-x Ce x Fe 2-x V x O6 ( x =0.6~1); The raw materials for preparing lanthanum ferrite magneto-optical film include La2O3, CeO2, Fe2O3, Fe and V2O5, and are prepared on quartz glass and single crystal silicon as substrates. The crystal phase is a cubic double perovskite structure with a space group of Fm -3 m ; Among them, Ce and La jointly occupy the A site, and Fe and V jointly occupy the B site.
[0016] Embodiment 2 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.4 Ce 0.6 Fe 1.4 V 0.6 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were accurately weighed, and the weighed 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were once ground in a corundum mortar to obtain a once-ground polycrystalline powder; It should be noted that the Fe source comes from Fe and Fe2O3.
[0017] Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with quartz glass as the substrate and Ar as the working gas. 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / SiO2 film; Step 4: Use a quartz vacuum tube furnace to 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / SiO2 film was annealed to obtain fully crystallized La 1.4 Ce0.6 Fe 1.4 V 0.6 O6 / SiO2 thin film.
[0018] Furthermore, in the process of obtaining the polycrystalline powder ground once, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 30 min, and the pressure of the primary pressing was 30 MPa; in the process of obtaining the polycrystalline powder sintered once, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 h; in the process of obtaining the polycrystalline target material sintered twice, the dosage of polyvinyl alcohol adhesive was 5 ml, the secondary grinding time was 1 h, the secondary pressing pressure was 30 MPa, the thickness of the target material pressed twice was 5 mm, and the secondary sintering temperature was 850°C.
[0019] Preparation of La using Ar as working gas 1.4 Ce 0.6 Fe 1.4 V 0.6 In the process of O6 / SiO2 film, the target-substrate distance is 10 cm and the background vacuum is less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 1h.
[0020] Obtaining fully crystallized La 1.4 Ce 0.6 Fe 1.4 V 0.6 During the process of forming O6 / SiO2 film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0021] Embodiment 3 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.4 Ce 0.6 Fe 1.4 V 0.6 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were accurately weighed, and the weighed 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were once ground in a corundum mortar to obtain a once-ground polycrystalline powder; It should be noted that the Fe source comes from Fe and Fe2O3.
[0022] Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with Si (100) oriented single crystal silicon as the substrate and Ar as the working gas. 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / Si(100) film; Step 4: Use a quartz vacuum tube furnace to 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / Si(100) film was annealed to obtain fully crystallized La 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / Si(100) thin film.
[0023] Furthermore, in the process of obtaining the polycrystalline powder ground once, the ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 30 min, and the pressure of the primary pressing was 30 MPa; in the process of obtaining the polycrystalline powder sintered once, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 h; in the process of obtaining the polycrystalline target material sintered twice, the dosage of polyvinyl alcohol adhesive was 5 ml, the secondary grinding time was 1 h, the secondary pressing pressure was 30 MPa, the thickness of the target material pressed twice was 5 mm, and the secondary sintering temperature was 850°C.
[0024] Preparation of La using Ar as working gas 1.4 Ce 0.6 Fe 1.4 V 0.6 During the process of O6 / Si(100) film deposition, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 1h.
[0025] Obtaining fully crystallized La 1.4 Ce0.6 Fe 1.4 V 0.6 During the annealing process of O6 / Si(100) film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0026] Embodiment 4 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.4 Ce 0.6 Fe 1.4 V 0.6 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were accurately weighed, and the weighed 35.40 g of La2O3 raw material, 16.03 g of CeO2 raw material, 8.67 g of Fe2O3 raw material, 6.07 g of Fe raw material and 8.47 g of V2O5 raw material were once ground in a corundum mortar to obtain a once-ground polycrystalline powder; It should be noted that the Fe source comes from Fe and Fe2O3.
[0027] Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with Si (111) oriented single crystal silicon as the substrate and Ar as the working gas. 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / Si(111) thin film; Step 4: Use a quartz vacuum tube furnace to 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 / Si(111) thin film was annealed to obtain fully crystallized La 1.4 Ce 0.6 Fe1.4 V 0.6 O6 / Si(111) thin film.
[0028] Furthermore, in the process of obtaining the polycrystalline powder ground once, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 30 min, and the pressure of the primary pressing was 30 MPa; in the process of obtaining the polycrystalline powder sintered once, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 h; in the process of obtaining the polycrystalline target material sintered twice, the dosage of polyvinyl alcohol adhesive was 5 ml, the secondary grinding time was 1 h, the secondary pressing pressure was 30 MPa, the thickness of the target material pressed twice was 5 mm, and the secondary sintering temperature was 850°C.
[0029] Preparation of La using Ar as working gas 1.4 Ce 0.6 Fe 1.4 V 0.6 During the O6 / Si(111) film deposition process, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 1h.
[0030] Obtaining fully crystallized La 1.4 Ce 0.6 Fe 1.4 V 0.6 During the O6 / Si(111) film annealing process, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0031] Embodiment 5 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.2 Ce 0.8 Fe 1.2 V 0.8 According to the stoichiometric ratio of O6, 30.38g of La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were accurately weighed, and the weighed La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were ground in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with quartz glass as the substrate and Ar as the working gas. 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / SiO2 film; Step 4: Use a quartz vacuum tube furnace to 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / SiO2 film was annealed to obtain fully crystallized La 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / SiO2 thin film.
[0032] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 35 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the furnace temperature of the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the second grinding time was 1 hour, the second pressing pressure was 30 MPa, and the second sintering temperature was 850°C.
[0033] Preparation of La using Ar as working gas 1.2 Ce 0.8 Fe 1.2 V 0.8 In the process of O6 / SiO2 film, the target-substrate distance is 10 cm and the background vacuum is less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 2h.
[0034] Obtaining fully crystallized La 1.2 Ce 0.8 Fe 1.2 V 0.8During the process of forming O6 / SiO2 film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0035] Embodiment 6 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.2 Ce 0.8 Fe 1.2 V 0.8 According to the stoichiometric ratio of O6, 30.38g of La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were accurately weighed, and the weighed La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were ground in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with Si (100) oriented single crystal silicon as the substrate and Ar as the working gas. 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(100) film; Step 4: Use a quartz vacuum tube furnace to 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(100) film was annealed to obtain fully crystallized La 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(100) thin film.
[0036] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 35 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the furnace temperature of the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the second grinding time was 1 hour, the second pressing pressure was 30 MPa, and the second sintering temperature was 850°C.
[0037] Preparation of La using Ar as working gas 1.2 Ce 0.8 Fe 1.2 V 0.8 During the process of O6 / Si(100) film deposition, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 2h.
[0038] Obtaining fully crystallized La 1.2 Ce 0.8 Fe 1.2 V 0.8 During the annealing process of O6 / Si(100) film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0039] Embodiment 7 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.2 Ce 0.8 Fe 1.2 V 0.8 According to the stoichiometric ratio of O6, 30.38g of La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were accurately weighed, and the weighed La2O3 raw material, 21.40g of CeO2 raw material, 7.44g of Fe2O3 raw material, 5.21g of Fe raw material and 11.31g of V2O5 raw material were ground in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering with Si (111) oriented single crystal silicon as the substrate and Ar as the working gas. 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(111) thin film; Step 4: Use a quartz vacuum tube furnace to 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(111) thin film was annealed to obtain fully crystallized La 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 / Si(111) thin film.
[0040] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 35 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the furnace temperature of the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the second grinding time was 1 hour, the second pressing pressure was 30 MPa, and the second sintering temperature was 850°C.
[0041] Preparation of La using Ar as working gas 1.2 Ce 0.8 Fe 1.2 V 0.8 During the O6 / Si(111) film deposition process, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 2h.
[0042] Obtaining fully crystallized La 1.2 Ce 0.8 Fe 1.2 V0.8 During the O6 / Si(111) film annealing process, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0043] Embodiment 8 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 stoichiometric ratio, accurately weigh 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material, grind the weighed 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The target sheet of the secondary sintering is prepared by radio frequency magnetron sputtering with quartz glass as the substrate and Ar as the working gas. 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / SiO2 film; Step 4: Use a quartz vacuum tube furnace to 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / SiO2 film was annealed to obtain fully crystallized La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / SiO2 thin film.
[0044] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 40 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the time for the second grinding was 1 hour, the pressure of the second pressing was 30 MPa, and the temperature of the second sintering was 850°C.
[0045] Preparation of La using Ar as working gas 1.0 Ce 1.0 Fe 1.0 V 1.0 In the process of O6 / SiO2 film, the target-substrate distance is 10 cm and the background vacuum is less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 3h.
[0046] Obtaining fully crystallized La 1.0 Ce 1.0 Fe 1.0 V 1.0 During the process of forming O6 / SiO2 film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0047] Embodiment 9 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 stoichiometric ratio, accurately weigh 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material, grind the weighed 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The target sheet of the secondary sintering is prepared by radio frequency magnetron sputtering with Si (100) oriented single crystal silicon as the substrate and Ar as the working gas. 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(100) film; Step 4: Use a quartz vacuum tube furnace to 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(100) film was annealed to obtain fully crystallized La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(100) thin film.
[0048] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 40 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the time for the second grinding was 1 hour, the pressure of the second pressing was 30 MPa, and the temperature of the second sintering was 850°C.
[0049] Preparation of La using Ar as working gas 1.0 Ce 1.0 Fe 1.0 V 1.0 During the process of O6 / Si(100) film deposition, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 3h.
[0050] Obtaining fully crystallized La 1.0 Ce 1.0 Fe 1.0 V1.0 During the annealing process of O6 / Si(100) film, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0051] Embodiment 10 This embodiment provides a Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, the method comprising the following steps: Step 1. Follow La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 stoichiometric ratio, accurately weigh 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material, grind the weighed 25.37g of La2O3 raw material, 26.80g of CeO2 raw material, 6.22g of Fe2O3 raw material, 4.35g of Fe raw material and 14.16g of V2O5 raw material in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding, the secondarily ground polycrystalline powder is secondarily pressed in a two-inch round stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The target sheet of the secondary sintering is prepared by radio frequency magnetron sputtering with Si (111) oriented single crystal silicon as the substrate and Ar as the working gas. 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(111) thin film; Step 4: Use a quartz vacuum tube furnace to 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(111) thin film was annealed to obtain fully crystallized La 1.0 Ce 1.0 Fe 1.0 V 1.0 O6 / Si(111) thin film.
[0052] Furthermore, in the process of obtaining the raw material for the first grinding, the molar ratio of iron to ferric oxide was 2:1, the grinding time by corundum mortar was 40 minutes, and the pressure of the first pressing was 30 MPa; in the process of obtaining the polycrystalline target material for the first sintering, the temperature in the high-temperature tube furnace was 800°C, and the vacuum sintering time was 12 hours; in the process of obtaining the polycrystalline target material for the second sintering, the dosage of polyvinyl alcohol adhesive was 5 ml, the time for the second grinding was 1 hour, the pressure of the second pressing was 30 MPa, and the temperature of the second sintering was 850°C.
[0053] Preparation of La using Ar as working gas 1.0 Ce 1.0 Fe 1.0 V 1.0 During the O6 / Si(111) film deposition process, the target-substrate distance was 10 cm and the background vacuum was less than 3.6×10 -4 Pa, working gas pressure 1.0Pa, gas flow rate 30Sccm, sputtering power 70W, and sputtering time 3h.
[0054] Obtaining completely crystallized La with different thicknesses 1.0 Ce 1.0 Fe 1.0 V 1.0 During the O6 / Si(111) film annealing process, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
[0055] In order to verify the effectiveness of the present invention, 3+ The properties of cubic lanthanum ferrite magneto-optical films were evaluated; After annealing, La 1.4 Ce 0.6 Fe 1.4 V 0.6 O6 film, La 1.2 Ce 0.8 Fe 1.2 V 0.8 O6 thin film and La 1.0 Ce 1.0 Fe 1.0 V 1.0 The crystal structure of O6 thin film was characterized, and the obtained XRD spectrum was as follows Figure 1 As shown in the figure, after annealing at 750℃, the film has been completely crystallized, and multiple diffraction peaks appear in the XRD spectrum, all of which belong to the reference LaSrFeVO6 cubic double perovskite calcium phase standard card (JCPDS54-0757). This shows that through the tolerance factor t By regulating the LaFeO3 phase, it was successfully transformed from the orthorhombic phase to the cubic phase.
[0056] from Figure 2 It can be seen from (a) that after annealing, only the diffraction peak of the (200) plane appears in the LaCeFeVO6 film sputtered on Si (100) for 1 h, which indicates that the lattice fit between the Si (100) substrate and the (100) plane of the LaCeFeVO6 film is high, and a single crystal film with a specific preferred orientation can be obtained by sputtering a certain thickness. The diffraction peak here is slightly offset compared with the standard card (JCPDS 54-0757), which is mainly due to the Ce 3+ The ionic radius is larger than that of Sr 2+ Therefore, the lattice constant of LaCeFeVO6 is theoretically slightly smaller than that of LaSrFeVO6, which causes the diffraction peak to shift to a higher angle. Figure 2 It can also be seen in (a) that in the LaCeFeVO6 film sputtered on the Si(111) substrate for 1h, in addition to the (111) plane, there are also (222) and (422) plane diffraction peaks, and the film sputtered for 3h also has the above multiple diffraction peaks. This shows that the lattice compatibility between Si(111) and LaCeFeVO6 film is not as good as that of Si(100). In addition, as the sputtering time increases to 3h, the preferential growth orientation of the film decreases. This is because as the film thickness increases, the stress state inside the film and at the interface will change, thus affecting the crystal orientation.
[0057] In order to reduce the influence of the single crystal Si substrate on the XRD diffraction spectrum and obtain more crystal phase information, the LaCeFeVO6 / Si film was also tested by grazing incidence diffraction (GIXRD). The results are shown in Figure 2. Figure 2 As shown in (b) in the figure: Compared with the XRD spectrum, the diffraction peak of the Si base in the GIXRD spectrum is significantly weakened, and only a weak impurity peak that does not belong to the LaCeFeVO6 film is detected near 2θ=28°, which is mainly derived from the Si substrate and the SiO2 natural oxide film on its surface. Figure 2 It can also be seen in (a) that the detected film diffraction peaks all belong to the standard diffraction spectrum of the double perovskite cubic phase. Among them, the film diffraction peaks sputtered for 3h appear more, which is basically consistent with the XRD spectrum results.
[0058] In summary, pure double perovskite cubic LaCeFeVO6 thin films were successfully prepared on SiO2, Si(100) and Si(111) substrates. Among them, LaCeFeVO6 thin films with (100) surface high preferential growth orientation can be obtained after sputtering for 1h and vacuum annealing at 750℃ on Si(100) substrate. This shows that the cubic double perovskite structure has a high lattice fit with silicon single crystals, and high-quality thin films can be grown epitaxially on silicon.
[0059] In materials science and semiconductor technology, choosing the right crystal plane for growth is crucial to the quality and performance of thin films. Si(100) and Si(111) are two common crystal planes of silicon. The degree of lattice matching between them and thin films directly affects the growth quality, stress state and final application performance of the thin films. The cross-sectional morphology of LaCeFeVO6 thin films prepared on Si(100) and Si(111) substrates was analyzed by scanning electron microscopy. The results are shown in Figure 2. Figure 3 As shown. Figure 3 In (a), it can be clearly observed that the LaCeFeVO6 film is well bonded to the Si(100) substrate, the grain growth is dense and uniform, and there are fewer grain boundaries between the grains. The thickness of the film sputtered on the substrate for 1 hour is 123nm. Figure 3 In (b), it can be observed that some holes and defects appeared in the thin film prepared on Si (111) after crystallization, and the film quality was not as good as that of LaCeFeVO6 / Si (100). The thickness of the LaCeFeVO6 film sputtered for 1 hour on this substrate was 130 nm. Figure 2 From the analysis of the results in (a), it can be seen that this is mainly because the atomic arrangement of the Si(100) crystal plane is more compatible with the LaCeFeVO6 film, which is conducive to obtaining a highly oriented, high-quality film.
[0060] In addition, the surface morphology of the film also has a great influence on its optical properties. If the surface is too rough or has cracks, it will lead to strong grain boundary scattering, causing optical loss, and will also have an adverse effect on the magneto-optical properties of the film. Figure 4 (a) in Figure 4 and (b) in Figure 4 are AFM images of LaCeFeVO6 / Si(100) films after crystallization after sputtering for 1h and 3h, respectively. Figure 4 It can be seen from (a) that after annealing, the film forms uniform grains, the surface is smooth and crack-free, and the particles are evenly distributed. The root mean square roughness Rq value of the LaCeFeVO6 / Si(100) film sputtered for 1h is only 3.14nm. As the thickness of the film increases, the crystallized particle size will increase relatively. The root mean square roughness Rq value of the LaCeFeVO6 / Si(100) film sputtered for 3h after annealing increases to 8.76nm, as shown in Figure 1. Figure 4As shown in (b) in the figure. Overall, the film has a good surface morphology, uniform grain distribution, and the roughness is kept below 10 nm. The Rq value of the garnet-type magneto-optical film reported in the literature reached 11.2nm, and cracking occurred. In comparison, the cubic double perovskite LaCeFeVO6 film grown on a silicon substrate has better film quality, especially the film prepared on Si(100) substrate. The grains after annealing are uniform and dense, without holes and defects, and there is no tendency to form wrinkles or cracks. The Rq value is only 3.14nm, which is significantly reduced compared with the garnet-type silicon-based magneto-optical film.
[0061] Given that Ce 3+ Ions can enhance Fe 3+ The spin-orbit splitting of the 3d excited state of ions is achieved by doping an appropriate amount of Ce into rare earth ferrites. 3+ The magneto-optical properties of the material can be improved. 3+ It is metastable and can be easily oxidized into more stable non-magnetic Ce. 4+ , which will have an adverse effect on the magneto-optical effect of the material. In addition, the concentration distribution of Fe with different valence states will also affect the magnetic properties of the material, and Fe 2+ Ions have strong absorption in the near-infrared region, which will reduce the optical transmittance of the film to a certain extent and increase light loss. In view of this, the present invention analyzes the valence state of all elements in the LaCeFeVO6 / Si film after vacuum annealing. The results are as follows: Figure 5 shown.
[0062] Figure 5 (a) is the XPS spectrum of La3d thin film. According to the literature reports, the binding energy peaks at 851.5 and 835 eV are respectively attributed to La 3+ 3d 3 / 2 and 3D 5 / 2 The characteristic peaks at 855.8 and 839 eV are the corresponding satellite peaks. It can be seen that all La ions in the prepared LaCeFeVO6 / Si film are +3 valence. The XPS spectrum of Ce3d film and its fitting spectrum are shown in Figure 5 As shown in (b) of the figure, it can be observed that the Ce3dXPS spectrum of the film has two strong peaks in the range of 878~890eV and 895~910eV. According to the analysis of the Ce3dXPS spectrum, the peaks at 881.3eV, 885.8eV, 899.5eV and 903.6eV are all attributed to Ce. 3+ ions. 4+ The binding energy peak of Figure 5 This does not appear in (b), which indicates that Ce in LaCeFeVO6 / Si film is all +3.
[0063] Figure 5 (c) is the Fe2pXPS spectrum of LaCeFeVO6 / Si film and its fitting spectrum. According to the literature, the multiple peaks at 710.3eV and 712eV can be attributed to Fe 3+ 2p 3 / 2 , and its satellite peak (sat.) is located at 718eV. 3+ 2p 1 / 2 The characteristic peak and satellite peak of are located at 724eV and 731.8eV respectively. Figure 5 From (c) in the figure, we can see that the iron elements in LaCeFeVO6 / Si film are all Fe 3+ ion. Figure 5 (d) is the V2p XPS spectrum of LaCeFeVO6 / Si film. In addition, since the binding energy position of O1s is close to that of V2p, Figure 5 According to relevant literature reports, the binding energy peaks at 516.3eV and 524eV are V 4+ 2p 3 / 2 and V 4+ 2p 1 / 2 In addition, the binding energy at 530 eV is attributed to the lattice oxygen (O 2− 1s). Due to some Fe 3+ Ions are high-valent V 4+ Instead, in order to maintain the conservation of charge, there is an excess of oxygen on the surface of the film, and there is some adsorbed oxygen with a binding energy peak at 532 eV.
[0064] In summary, the vacuum annealing treatment of the present invention has a good effect, which keeps the Ce ions at a low Ce 3+ state, Fe also remains in Fe 3+ Therefore, the magneto-optical properties and optical transmittance of the film will not be affected by the ion valence change.
[0065] The optical transmittance of the film has a certain influence on its practical application. Figure 6 The transmission spectrum of the crystallized LaCeFeVO6 / Si film in the UV-visible-near infrared region. As can be seen from the figure, the absorption edge of the film is around 950nm, which is mainly affected by the absorption edge of the substrate. After the LaCeFeVO6 / Si(100) film sputtered for 1h is crystallized, the transmittance can reach 60~70% in the 1000~3000nm band, which is significantly higher than the silicon substrate (50%). This is mainly because the silicon wafer itself has a large absorption. When a certain thickness of film is coated, its transmittance will be improved due to the anti-reflection effect.
[0066] In addition, the transmission curve of the film is relatively smooth, which is because the refractive index of the Si substrate and the perovskite ferrite is relatively close, and the light interference effect is weak. And there is no obvious absorption peak in the transmission spectrum of the cubic phase LaCeFeVO6 / Si(100) film, indicating that the film quality of the prepared silicon-based film is high and the optical transmission performance is good. The transmittance of the LaCeFeVO6 / Si(111) film sputtered for 1h after annealing is slightly lower than that of the film prepared on the Si(100) substrate. Combined with the SEM test results, it can be seen that this is mainly due to the fact that its film quality is relatively inferior to that of the film prepared on the Si(100) substrate. After crystallization, some holes and defects appear, which makes the grain boundary scattering generated when light passes through the film stronger, resulting in a weakening of its transmission performance, but it is still higher than the Si substrate, and there is no obvious absorption, and no light interference effect occurs. In general, the transmission performance is relatively good.
[0067] In summary, LaCeFeVO6 / Si film has good optical transmittance, especially in the near-infrared light region, and has no obvious absorption, so it can have low optical loss, which is conducive to its application in silicon-based magneto-optical integrated devices.
[0068] Figure 7 (a) and Figure 7 (b) shows the room temperature saturation hysteresis loop spectra of LaCeFeVO6 films prepared on Si(100) and Si(111) substrates, respectively. The maximum applied magnetic field is 18000Oe, and the directions are perpendicular to the film surface (out-of-plane) and parallel to the film surface (in-plane). The results show that LaCeFeVO6 / Si film has strong magnetism, and the highest saturation magnetization can reach 90emu / cm 3 , which is significantly higher than the Sr,V:CeFeO3 / Si magneto-optical film with the same perovskite cubic phase. Under the same doping concentration, the saturation magnetization intensity of the film is only 35.5emu / cm 3 This is mainly due to La 3+ The ions are magnetic, and Sr 2+ It is non-magnetic, so under the same doping ratio, the magnetism of La, V: CeFeO3 will be better than that of Sr, V: CeFeO3. Since Sr, V: CeFeO3 has been reported to have a strong magneto-optical effect, the LaCeFeVO6 prepared by the present invention will theoretically have better magneto-optical properties.
[0069] In addition, for magnetic recording materials, as the magnetic recording density of traditional in-plane magnetic recording media continues to increase, the demagnetization field of the magnetic recording bit particles will be significantly enhanced. This enhanced demagnetization field will not only cause the recording signal to be unstable, but also widen the transition region, limiting the increase in recording density. In order to solve the problem of improving magnetic recording density, a perpendicular recording method is proposed, that is, using a magnetic recording medium with perpendicular magnetic anisotropy to store information. Figure 7 (a) and Figure 7 From (b) in the figure, we can see that the saturation magnetization of LaCeFeVO6 / Si(100) in the vertical direction is 90emu / cm 3 , the saturation magnetization in the parallel direction is 50 emu / cm 3 , which is close to the saturation magnetization intensity of LaCeFeVO6 / Si(111) film (87.5emu / cm in the vertical direction). 3 , parallel direction is 49.5emu / cm 3 ). It can be seen that the easy magnetic axes of the two films are perpendicular to the film surface (out-of-plane) when the external magnetic field is applied, indicating that both have obvious perpendicular magnetic anisotropy, and the orientation of the substrate has no effect on their easy magnetization direction. Therefore, the LaCeFeVO6 / Si film prepared in this paper also has potential application prospects as a magnetic recording medium material.
[0070] The magneto-circular dichroism effect is caused by the different absorption coefficients of left-handed and right-handed circularly polarized light under the action of a magnetic field. It is the main technical means to study the magneto-optical properties of thin films and nanomaterials. At present, the research on magneto-optical effect is mainly carried out around garnet-type rare earth ferrites, while the research on Ce-containing 3+ However, there are few studies on the magneto-optical effect of perovskite films and the magnetic circular dichroism effect of this type of materials. Figure 8 This is the MCD spectrum of LaCeFeVO6 / SiO2 film, with an external magnetic field of 5000Oe. As can be seen from the figure, the LaCeFeVO6 film exhibits obvious magnetic circular dichroism effect at 435 and 595nm. 3+ Tanabe-Sugano plot, these peaks are attributed to 6 A 1g ( 6 S) → 4 E g ; 4 A 1g ( 4 G) and 6 A 1g ( 6 S) → 4 T 1g ( 4G). Especially at 435 nm, the MCD ellipticity |ψ F | Reaching 2770° / cm, its magneto-optical effect is significantly stronger than the popular magneto-optical material Ce 3+ :YIG epitaxial film (|ψ F |=1700° / cm, external magnetic field 5000 Oe). According to literature reports, Ce 3+ :The magneto-optical properties of YIG films are superior to those of commercial YIG and Bi 3+ :GIG(Bi 3+ :Gd3Fe5O 12 ). Given that the lattice matching degree between perovskite LaCeFeVO6 and silicon is higher than that between garnet and silicon, and its magneto-optical performance is more superior, it will have broader application prospects in the field of silicon-based magneto-optical integrated devices.
[0071] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A Ce-rich 3+ The cubic lanthanum ferrite magneto-optical film is characterized by: Lanthanum ferrite magneto-optical film is La 2- x Ce x Fe 2-x V x O6; The raw materials for preparing lanthanum ferrite magneto-optical film include La2O3, CeO2, Fe2O3, Fe and V2O5, and are prepared on quartz glass and single crystal silicon as substrates. The crystal phase is a cubic double perovskite structure with a space group of Fm -3 m ; Among them, Ce and La jointly occupy the A site, and Fe and V jointly occupy the B site.
2. A method for preparing the Ce-rich 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: The method comprises the following steps: Step 1. Follow La 2-x Ce x Fe 2-x V x The raw materials La2O3, CeO2, Fe2O3, Fe and V2O5 are weighed in a stoichiometric ratio of O6, and the weighed raw materials La2O3, CeO2, Fe2O3, Fe and V2O5 are ground once in a corundum mortar to obtain a once-ground polycrystalline powder; Step 2, the polycrystalline powder ground once is uniformly mixed, and after being uniformly mixed, it is pressed once by pressure to obtain the polycrystalline powder pressed once, and the polycrystalline powder pressed once is vacuum sintered in a high-temperature tube furnace to obtain the polycrystalline powder sintered once; the polycrystalline powder sintered once is secondarily ground by a polyvinyl alcohol adhesive to obtain the polycrystalline powder ground twice; after the second grinding is completed, the secondarily ground polycrystalline powder is secondarily pressed in a circular stainless steel mold to obtain the target material pressed twice, and the target material pressed twice is placed in a high-temperature tube furnace for second sintering to obtain the polycrystalline target material sintered twice; Step 3: The secondary sintered polycrystalline target is prepared by radio frequency magnetron sputtering using quartz glass, Si (100) or Si (111) oriented single crystal silicon as the substrate and Ar as the working gas. 2-x Ce x Fe 2-x V x O6 film; Step 4: Use a quartz vacuum tube furnace to 2-x Ce x Fe 2-x V x O6 film is annealed to obtain a completely crystallized La 2- x Ce x Fe 2-x V x O6 film.
3. A Ce-rich compound according to claim 2 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: In the process of obtaining the once-ground polycrystalline powder, the molar ratio of iron to ferric oxide is 2:1, the time for grinding the raw materials with the corundum mortar is 30 to 40 minutes, and the pressure for once pressing is 30 MPa.
4. A Ce-rich compound according to claim 2 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: In the process of obtaining the once-sintered polycrystalline powder, the temperature inside the high-temperature tube furnace is 800° C., and the vacuum sintering time is 12 hours.
5. A Ce-rich compound according to claim 2 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: In the process of obtaining the secondary sintered polycrystalline target material, the dosage of polyvinyl alcohol binder is 5 ml, the secondary grinding time is 1 hour, the secondary pressing pressure is 30 MPa, the secondary pressed target material thickness is 5 mm, and the secondary sintering temperature is 850°C.
6. A Ce-rich compound according to claim 2 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: Preparation of La using Ar as working gas 2-x Ce x Fe 2-x V x In the process of O6 film, the target-substrate distance is 10 cm, and the background vacuum is less than 3.6×10 -4 Pa, the working gas pressure is 1.0Pa, the gas flow rate is 30Sccm, the sputtering power is 70W, and the sputtering time is 1~3h.
7. A Ce-rich compound according to claim 2 3+ A method for preparing a cubic phase lanthanum ferrite magneto-optical film, characterized in that: Obtaining fully crystallized La 2-x Ce x Fe 2-x V x During the O6 film annealing process, the annealing temperature of the quartz vacuum tube furnace was 750°C, the annealing constant temperature time was 4h, and the heating and cooling rates were controlled at 1°C / min.
8. A Ce-rich 3+ The application of a cubic phase lanthanum ferrite magneto-optical film, wherein the lanthanum ferrite magneto-optical film is prepared by the preparation method according to any one of claims 2 to 7, characterized in that: The cubic phase lanthanum ferrite magneto-optical film is applied to an optical isolator, an optical circulator or a magneto-optical modulator.